Hamming weights in irreducible cyclic codes - Ding, Cunsheng; Yang, Jing (Discrete mathematics, 2013)
The objectives of this paper are to survey and extend earlier results on the weight distributions of irreducible cyclic codes, present a divisibility theorem and develop bounds on the weights in irreducible cyclic codes.